Social Media As A Place Of False Happiness - Widari, Ni Nyoman Tri Puspa; Wulanyani, Ni Made Swasti (Yayasan Sinergi Kawula Muda, 2023)
Subjective happiness is defined as a person's assessment of life which tends to be personal. Subjective happiness is often associated with false happiness shown by someone. This is consistent with the purpose of this study, which is to see the image of social media as a place of false happiness. This study uses a descriptive qualitative approach with respondents consisting of active social media users and have experience in building images of happiness on social media platforms with data collection procedures using literature studies and analysis of social media content as well as interviews with celebrities. The results of this study indicate that many people are lulled by pseudo-even fake happiness on social media. Authentic happiness can be generated through self-assessment and identifying and cultivating fundamental strengths that can be achieved by developing the six values, namely wisdom and knowledge, passion and passion, humanity and love, fairness, temperament, and transcendence.